Politik Uang: (Reunderstanding Inflasi dan Kurs dalam Ekonomi Islam) - Atok Syihabuddin; Bakhrul Huda; Binti Nur Asiyah (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2022)
Money is the blood of economic life, and its circulation requires financial institutions in the form of a monetary system for monetary control. One of the things that are feared by the modern monetary system is inflation, which is a symptom of a general and continuous increase in the price of goods, which can be caused by natural things such as supply and demand or caused by human error or caused by fluctuations domestic currency exchange rate. In Islamic Economics, the role of money as a medium of exchange has made it a tool for balancing a commodity, which in turn can impact inflation. Therefore, as recommended by the Prophet Muhammad, money cannot be used as a fair and honest exchange rate in anticipation of avoiding financial instability. Steps are required: spot exchange of money; expedited wages; zakat, infaq and alms; prohibition of monopoly on the distribution of wealth; usury prohibition; and prohibition of price fixing.   Abstrak: Uang merupakan darah dalam kehidupan berekonomi, di mana peredarannya membutuhkan keberadaan lembaga keuangan berupa sistem moneter guna pengendalian moneter. Salah satu hal yang ditakuti oleh sistem moneter modern adalah inflasi, yaitu sebuah gejala kenaikan harga barang yang bersifat umum dan terus-menerus, yang bisa diakibatkan oleh hal-hal bersifat alamiyah seperti supply and demand, atau disebabkan human error, atau disebabkan oleh naik turunnya kurs mata uang domestic. Dalam konsep Ekonomi Islam, peran uang sebagai medium of exchange telah menjadikannya mengambil alih sebagai timbangan bagi suatu komoditas, yang pada ujungnya bisa berdampak pada inflasi. Oleh karena itu, uang tidak dapat digunakan sebagai nilai tukar yang adil dan jujur. Sebagai antisipasi guna menghindari instabilitas keuangan, sebagaimana anjuran Rasulullah saw. diperlukan langkah-langkah: tukar-menukar uang secara spot; menyegerakan upah; zakat, infak dan sedekah; larangan monopoli peredaran kekayaan; larangan riba; dan larangan penentuan harga.